2016
DOI: 10.1016/j.jaci.2015.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Atopic endotype in childhood

Abstract: We found very little interdependency between asthma, eczema, and allergic sensitization through childhood. The associations between those entities were strongly dependent on age, type of allergens, and method of testing for sensitization. Therefore, atopy in children is unlikely to represent a true endotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 34 publications
5
37
1
Order By: Relevance
“…Thus far, all previous studies have shown that isolated late‐onset sensitization is not a risk factor for asthma . We have previously shown an association between any sensitization at 13 years and current asthma, but in this study, we found no association between late‐onset sensitization (sensitization only at 13 years) and current asthma, indicating that the persistent sensitization group is driving the former finding. It should, however, be noted that we found a borderline significant association between late‐onset sensitization diagnosed by sIgE and asthma ( P = .10), and the result should be interpreted with caution as the low number of cases with late‐onset sensitization (N = 27) may mask a true association (type II error).…”
Section: Discussioncontrasting
confidence: 87%
“…Thus far, all previous studies have shown that isolated late‐onset sensitization is not a risk factor for asthma . We have previously shown an association between any sensitization at 13 years and current asthma, but in this study, we found no association between late‐onset sensitization (sensitization only at 13 years) and current asthma, indicating that the persistent sensitization group is driving the former finding. It should, however, be noted that we found a borderline significant association between late‐onset sensitization diagnosed by sIgE and asthma ( P = .10), and the result should be interpreted with caution as the low number of cases with late‐onset sensitization (N = 27) may mask a true association (type II error).…”
Section: Discussioncontrasting
confidence: 87%
“…40 Asthma and atopy frequently coexist in children but this concordance decreases over time and does not prove that the asthma is due to the atopy. 41,42 In adults, asthma frequently occurs without atopy. 43 For these reasons, our finding of protective associations with early-life exposure predominantly for atopy, rather than asthma, may not be surprising.…”
Section: Discussionmentioning
confidence: 99%
“…The manifestations may present in a characteristic sequence in children that has been named the atopic or allergic march [2]. Although the atopic march is highly controversial and only a minority of patients follow this march [3], the first signs of atopic diseases are usually food allergy and atopic dermatitis. As these signs of atopic disease are often observed in the first 3 years of life and are thought to be related to the maturation of the immune system [2].…”
Section: Introductionmentioning
confidence: 99%